INFLUENCE OF PRODUCT INNOVATION AND SERVICE QUALITY ON PURCHASE DECISION IN JAMBI ARINY BATIK IN KELURAHAN PASIR PANJANG JAMBI KOTA SEBERANG - Agesha Marsyaf (Journal of Business Studies and Management Review, 2021)
Batik is a national cultural asset that has been inherited from generation to generation to every generation until now. Batik represents one of the creative handicraft industries in Indonesia which is rooted in culture and is able to provide employment and entrepreneurship in Indonesia, one of which is the Jambi area. Like other products, in order to be able to compete in the Jambi batik product market, it is necessary to understand the market's needs. Therefore, the authors took the title "The Effect of Product Innovation and Service Quality on Purchasing Decisions in Batik Jambi Ariny in the Kelurahan Pasir Panjang Jambi, Kota Seberang".The method used is a survey method. The data used are primary data obtained from direct interviews using a questionnaire. Data obtained through multiple linear regression analysis using the SPSS application.The results showed that product innovation and service quality had a positive and significant impact on purchasing decisions. On Batik Jambi Ariniy. Meanwhile, innovation and service quality simultaneously contributed 42.3% to the purchasing decision at Batik Jambi Ariny.